PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, PERILAKU KERJA INOVASI KERJA TERHADAP KINERJA TUGAS DI LPMP PROVINSI BANTEN - Yumhi Yumhi (Universitas La Tansa Mashiro, 2021)
This study aims to find factors that can explain task performance at LPMP Provinsi Banten. The analysis was carried out by examining the effect of transformational and transactional leadership, work behavior, and work innovation on task performance. The research approach used a quantitative survey from a total population of 87 people. 72 samples came from LPMP employees of Provinsi Banten. An interesting finding from this study is the partial and simultaneous effect of the dependent and independent variables. Simultaneous testing by paying attention to the R Square value of 0.540, means that simultaneously the effect of transformational and transactional leadership, work behavior, and work innovation on task performance is 54% while the remaining 46% is influenced by other factors outside of this research model. These results conclude that simultaneously and partially, transformational and transactional leadership, work behavior, and work innovation can be used as predictor variables for task performance. The findings show that leaders must realize that increasing transformational leadership styles, work behavior, work innovation will help improve employee task performance by providing motivation, providing equal opportunities, competency-based training, strengthening the sense of kinship among employees, bringing people together with suitable jobs and positions. , provides clarity of tasks and targets that must be achieved and encourages employees to work actively by providing rewards for outstanding employees. This method will boost the morale of other employees to make the best achievements for the Institute.